Juvenile Cosmology; Or Richard Powers’ Post-Global Doughnut - Judith Roof (Transatlantica)
Richard Powers’ novel Operation Wandering Soul (1993) enacts the canny link between an already jaded and out-dated globalism and the child as an ascendant category. Two sides of a snaking moebius enwrapping endlessness and timelessness, the novel’s tailing infinities—the universe and the child—recalibrate the scope, conception, narrative structure, and style of the novel as a genre. Moving from the Aristotelean to the Einsteinian, Operation Wandering Soul’s terrain is cosmological, while its narrative collapses time/space into an exhibition of something like Richard Feynman’s “sum over the histories” made up of proliferating versions of juvenile massings and vain pilgrimages. The novel’s collapse of time/space is not a simplistic paean to the global (a category already as out-dated as hapless Vietnam vets), but instead bags the gathering consciousness of an originless existence forever extending beyond its supposed coordinates. The novel wraps both inward and out, framing its frames and detours while loosing them. It spins tales like a revolving planet, wheeling solar system, or careening galaxy. The consciousness enacted by Operation Wandering Soul is not defined, thus, only as the perspective of its wandering soul surgeon protagonist Kraft, but as the accruing of all time and place, layered as an enactment of a complex and networked consciousness belonging to no one and everyone. Such accrual is a multi-perspectival echoing instigated by and instigating the act of reading, where reading itself constitutes the physics of the forgotten.